Pregnancy loss following miscarriage and termination of pregnancy for medical reasons during the COVID-19 pandemic: a thematic analysis of women's experiences of healthcare on the island of Ireland - Suzanne Heaney; Martina Galeotti; Áine Aventin (BMC, 2023)
Abstract Background Losing a baby during pregnancy can be a devastating experience for expectant parents. Many report dedicated, compassionate healthcare provision as a facilitator of positive mental health outcomes, however, healthcare services have been severely impacted during the COVID-19 pandemic. Aim To explore women's experiences of healthcare service provision for miscarriage and termination of pregnancy for medical reasons (TFMR) on the island of Ireland during the COVID-19 pandemic. Methods Findings combine data from elements of two separate studies. Study 1 used a mixed methods approach with women who experienced miscarriage and attended a hospital in Northern Ireland. Study 2 was qualitative and examined experiences of TFMR in Northern Ireland and Ireland. Data analysed for this paper includes open-ended responses from 145 women to one survey question from Study 1, and semi-structured interview data with 12 women from Study 2. Data were analysed separately using Thematic Analysis and combined for presentation in this paper. Results Combined analysis of results indicated three themes, (1) Lonely and anxiety-provoking experiences; (2) Waiting for inadequate healthcare; and (3) The comfort of compassionate healthcare professionals. Conclusions Women's experiences of healthcare provision were negatively impacted by COVID-19, with the exclusion of their partner in hospital, and delayed services highlighted as particularly distressing. Limited in-person interactions with health professionals appeared to compound difficulties. The lived experience of service users will be helpful in developing policies, guidelines, and training that balance both the need to minimise the risk of infection spread, with the emotional, psychological, and physical needs and wishes of parents. Further research is needed to explore the long-term impact of pregnancy loss during a pandemic on both parents and health professionals delivering care.